Skin Cancer Knowledge, Attitudes, and Behaviors in Collegiate Athletes - Courtney Hobbs; Vinayak K. Nahar; M. Allison Ford; Martha A. Bass; Robert T. Brodell (Journal of Skin Cancer)
Outdoor athletes represent an important group at risk for skin cancer because they are routinely exposed to high levels of ultraviolet radiation. The purpose of this study was to assess current skin cancer knowledge, attitudes, and behaviors among collegiate athletes. A modified version of the Melanoma Risk Behavior Survey was completed by 343 athletes attending a Southern University in the USA, generating an 87% response rate. Survey results demonstrated that the majority of the athletes do not limit their sun exposure and reported low levels of sun protective behaviors. In addition, athletes lacked knowledge about skin cancer and sun protection. Eighty-three percent of the athletes stated that tanning beds improve one’s overall health. Race was significantly associated with skin cancer knowledge, whereas, gender was found to be significantly associated with knowledge, attitudes, and behaviors towards skin cancer. Additionally, there was a significant relationship between knowledge and behavior, but not between attitude and behavior. This study highlights the need to educate athletes about the hazards of tanning to minimize UV exposure and promote sun protection habits. Moreover, athletes should be educated on the dangers of indoor tanning facilities and encouraged to avoid these facilities.